016 Perspectives of Partners on Addressing Unmet Sexual Needs Following Prostate Cancer Therapy. (1st May 2022) - Li, R.; Wittmann, D.; Nelson, C.J.; Salter, C.A.; Mulhall, J.P.; Byrne, N.; Nolasco, T. Sanchez; Ness, M.; Gupta, N.; Cassidy, C.; Crisostomo-Wynne, T.; Loeb, S.
ABSTRACT: Introduction: Survivors of prostate cancer have reported physical and psychosocial sexual changes resulting from treatment of the disease that may challenge sexual recovery. Partners of prostate cancer patients experience sexual losses after patient treatment, yet their needs are not well understood and most resources do not incorporate partner priorities. Given that sexual intimacy requires mutuality, addressing unmet needs for partners is a key tenet in fostering sexual recovery for couples navigating the impact of prostate cancer treatment. Objective: The objective was to perform a qualitative study of partner focused sexual health-related themes that are relevant for couples' sexual recovery following prostate cancer therapy. Methods: We performed a qualitative study of posts to the Inspire Us TOO Prostate Cancer online support and discussion community, which connects > 31, 000 prostate cancer patients, family members, and caregivers. Text from anonymized, public available comments were reviewed from the prostate cancer and intimacy section. 6, 193 posts were identified, of which 661 were from female authors. A random sample of 10% of these posts (n = 66) were analyzed, as well as an equal number of posts from patients. Results: Multiple themes were discussed that reflect consensus in sexual health-related priorities across both patients and their partners. Patients and their partners identified similar challenges for sexual health after prostate cancer treatment, including coming to terms with changes in sexual function, frustration when interacting with clinicians, and barriers to access to sexual aids. Both parties frequently expressed appreciation for being able to share experiences with sexual recovery and sexual aids through forums such as online communities. However, several themes emerged that were unique to female partners. Partners were more likely to discuss the impact of sexual recovery on the couples' relations, but emphasized the relative importance of survival over sexual quality of life. Many partners also highlighted constructive mechanisms for aiding sexual recovery, such as expanding sexual repertoire with new techniques and utilizing psychosocial support and therapy. Notably, partners commonly expressed feeling that their needs for intimacy and sexuality were overlooked when couples sought support or resources from healthcare providers. Conclusions: Identifying unmet sexual needs for partners are critical for addressing barriers to sexual recovery following prostate cancer therapy. Our findings corroborate prior research in which partners reported feeling that their needs were excluded from addressing solutions to sexual health issues. Themes identified in this study can help the development of resources to improve sexual health support for partners of survivors of prostate cancer. They may also inform evaluation tools to assess partners' sexual quality of life. Disclosure: Work supported by industry: yes, by Department of Defense. A consultant, employee (part time or full time) or shareholder is among the authors (Gilead).